Generation and Expression of Recombinant Glutathione-S-Transferase full-length importin a-3 (GST-imp a-3) fusion protein and study of its role on the nuclear transport of protein - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Nuclear import of protein from cytoplasm into the nucleus occurs through nuclear pore complex (NPC) and typically requires a specific nuclear localization signal (NLS). Protein import mediated by transport receptor molecules importin a and B. Importin a is composed of a large central domain that consists of 10 tandemly repeated armadillo (arm) motif, which are organized in a superhelix flanked by small N and C terminus domain. The N terminus importin binding (IBB) domain of importin a mediates binding to importin 0. Importin a-3 is one of six importin a family member which has been identified in human. In the present study, to investigate the role of importin a-3 on nuclear transport of protein, it has been generated and expressed a recombinant glutathione-S-transferase full-length importin a-3 (GST-importin a-3) as fusion protein from expression plasmid pHM 1970. By co-immunoprecipitation the involvement of importin a-3 on the nuclear import of wild type recombinant hepatitis B core protein (WT rHBc) and simian virus 40 large T antigen (SV40 Tag) was determined. Then expression analysis of GST-importin a-3 fusion protein was determined by immunoblotting.